Legalitas Intervensi NATO Dalam Konflik Etnis di Kosovo Tahun 1999 - Gracia Mareta; Ayub Torry Satrio Kusumo; Anugrah Adiastuti (Faculty of Law Universitas Sebelas Maret, 2018)
This research proposes to analyze the validity of NATO intervention in the Kosovo conflict based on international law. The writing of this law belongs to the research of normative law which is prescriptive and applied. The legal materials of this study include primary and secondary legal materials. Collection techniques using literature study. Analytical techniques use deductive reasoning methods. The results showed NATO intervention in Kosovo violated international law, namely Article 2, Article 33, Article 37, and Article 42 of the UN Charter; Article 1 and Article 7 of NATO Treaty; Articles 51 and 52 of the Vienna Convention 1980; UN Security Council Resolution No. 1160, No. 1199, and No. 1203 and Article 2 of the Protocol III Convention on Certain Conventional Weapons in 1980, because NATO carried out air strikes with weapons prohibited in international humanitarian law and in the resolution filed by the UN Security Council stated that the solution to be pursued is diplomatic efforts, namely by finding a diplomatic solutions based on negotiation and taking comprehensive steps to reduce human tragedy, not military force.